2004
DOI: 10.1088/0964-1726/13/5/013
|View full text |Cite
|
Sign up to set email alerts
|

Fast Preisach modeling method for shape memory alloy actuators using major hysteresis loops

Abstract: The control accuracy of smart actuators, such as a shape memory alloy (SMA) or piezoceramic actuator, is limited due to their inherent hysteresis nonlinearities with a local memory, resulting from the influence of a previous input on subsequent behavior. In addition, the existence of minor loops in the major loop because of a local memory also makes the mathematical modeling and design of a controller difficult for SMA actuators. Therefore, to enhance the controllability of a smart actuator, the Preisach hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Song et al [43] presented the tracking control of a piezoceramic unimorph beam using the inverse Preisach model. Choi et al [44] presented a fast Preisach modeling method for SMA actuators using major hysteresis loops. Viswamurthy and Ganguli [45] discussed the modeling and compensation of piezoceramic actuator hysteresis for helicopter vibration control.…”
Section: Classical Preisach Modelmentioning
confidence: 99%
“…Song et al [43] presented the tracking control of a piezoceramic unimorph beam using the inverse Preisach model. Choi et al [44] presented a fast Preisach modeling method for SMA actuators using major hysteresis loops. Viswamurthy and Ganguli [45] discussed the modeling and compensation of piezoceramic actuator hysteresis for helicopter vibration control.…”
Section: Classical Preisach Modelmentioning
confidence: 99%
“…As it can be observed, in the figure, there is a discrepancy in experimental and simulation results. This can be attributed to the internal recovery, which is due to the formation of internal hysteresis loops when interrupting the cooling process [15,16]. However, the manipulator showed that any desirable position within the work space was achievable for a prescribed permissible error.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the modeling is difficult and the model equation is very complex. So even though this model is commonly used (Choi et al, 2004), the use of a heat transfer model and sensor hardware has been introduced.…”
Section: Sma Controlmentioning
confidence: 99%